A Causal Study Between Electricity Consumption and CO2 Emissions in India - Krishna Murthy, I. (Prabandhan: Indian Journal of Management, 2012)
This study examines the causal relationships between per-capita electricity consumption and per capita Co2 emissions for India covering the period 1971 to 2006 by using the cointegration and error correction models. Our study reveals that there exists co integration between the per capita Co2 emissions and per-capita electricity consumption. Both the time series per capita Co2 emissions and Electricity consumption are non stationary in level form, but are individually integrated of order one. Granger's causality test provided enough evidence of longer-term equilibrium relation between the two variables, which will attract the attention of policymakers in drawing out efficient policy making to drive the economy with less pollutant emissions. Empirical results have shown that up to lag 7, there exists a bilateral causality between the two variables that shows how these two variables are associated and there is a need for a closer look at the consumption of fossil fuels in generating and consuming the electricity in association with the environment. Further, VAR technique is used for forecasting the per capita Co2 emissions; the forecast for the future years are accurate with very mild forecast error.